Cellular layout formation by using weighted similarity-based modified flow matrix with process sequence data. (26th February 2020) - Shunmugasundaram, M.; Anbumalar, V.
Cellular layout formation (CLF) is an important problem in the design of a cellular manufacturing system (CMS). From the previous studies, most of the researchers have used machine part incidence matrix (MPIM) as input in CMS. In this paper, weighted similarity based modified flow matrix is proposed to solve the cell formation problem (CFP) and CLF simultaneously. The objective of our proposed approach is to group dissimilar machines based on the process sequence of different parts. Two well-known benchmark problems are selected from the literature and results are compared based on modified grouping efficacy with the existing methods. The results clearly indicated that our proposed approach outperforms the previously proposed methods.